(untitled) (Jurnal Geologi Pertambangan (JGP), 2016)
The Purpose of the research was to know the ramp condition from mining front up to disposal area at PIT Seam 12 of PT. Kitadin. And then it was also to evaluate the road condition in PT. Kitadin in doing removal overburden activity carried out by one of contractor of PT. Kitadin, it was PT. Arkananta. The result of observation and evaluation were used to be source to determining road geometry theoretically. Based on the result of observation, the result as followed : 1. The road length; working front up to disposal area, was ± 1,7 km. 2. The were some problems were occurred on the process of overburden, descreasing speed when vehicles were at certain interval in space in narrow road, bumpy road and wet road. In increasing the effectiveness of ramp was done several treatment to overcome problems were occurred in mining road at PIT Seam 12 as followed. First, road enlargement was unsuitable with theory of AASHTO ; 18,13 m on the straight road and 21,95 m on bend road. There were several point on temporary ramp was needed to be wider that was W12 +1.10 m, T2 +1.99 m, T4 +1.61 m, while finishing ramp was made exit PIT Seam 12. After getting several repair, there was positive effect to cycle time effecienly 16,12 minute became 14,52 minute. By decrasing of cycle time, time needed was propotional reversed with high dump truck was increased more than the first productivity ; 395,9 lcm/ hour became 439,5 lcm/ hour